The influence of magnetic field on the growth of tomato (Lycopersicum esculentum) infected with Fusarium oxysporum - Rochmah Agustrina; Endang Nurcahyani; Eko Pramono; Ika Listiana; Eko Nastiti (INSIST, 2016)
Abstract— This Previous research suggests that magnetic field (MF) can enhance seedling vigor, growth, and the production of tomato plants. This study examines the influence of MF on the growth of tomato infected by Fusarium oxysporum, fungal pathogen that causes Fusarium wilt in tomatoes. This factorial study arranged in a stripe split plot design. Factors tested consists of long exposure to the MF, M (control; 7'48 "; II'42" and 15'36 "), how to infect fusarium, F (through soaking the seeds and by infecting fusarium through the stem at the age 28 days after sowing (das), and soaking the seeds, S (soaking and without soaking for 15 minutes before MF treatment). Each unit of experiment was repeated 3 times. Parameters measured were percentage of germination, growth rate based on plant height, and fresh weight. Observations were made on the plant until 42 das. Data were analyzed of variance followed by the least significant difference (LSD) test at α = 1 and 5%. The results showed that the interaction between MF and fusarium (MxF), fusarium and soaking (FxS), and MF, fusarium, and soaking (MxFxS) did not produce a different response on all parameters measured. Differences in response to the treatments derived from the treatment of MF (M), Fusarium (F), and the treatment interaction of the MF x soaking (MxS). The MF (M) and the interaction of MF and soaking (MxS) significantly effect on all parameters measured at each measurement. The treatment of Fusarium (F) significantly effect on germination percentage, and fresh weight at 7 das.Keywords— magnetic field, fusarium, germination percentage, growth rate, fresh weight.